Relationships between housing prices and commuting flows - Arnstein Gjestland; Liv Osland; Inge Thorsen (European Regional Science Association (ERSA), 2010)
It has been argued that gravity models are the most popular mathematical description of human interaction (Sheppard, 1984). In relation to housing prices, gravity based accessibility measures have been suggested as a generalization of modern polycentric labour market structures (Heikkila et al. 1989). Empirical applications of gravity based accessibility measures are, however, fairly resource-demanding. As a determinant of housing prices, one aim of this paper is therefore to compare the performance of one such gravity based measure with simpler measures of mobility. In contrast with the gravity based measures which account for the potential of interaction, the measures introduced in this paper are based on actual commuting patterns. The paper shows that the relationship between housing prices and patterns of commuting is fairly complex and we use a range of different methods to obtain robust conclusions. Finally we try to analyse the effect of long term changes in population on house prices and to study the effect on house prices of a large transport infrastructure investment.
Keywords: 330